Cartel destabilization and leniency programs: Empirical evidence - Gordon J. Klein (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
Leniency programs as a tool for cartel detection and cartel destabilization, have been implemented since the early nineties. Theoretical work has shown that leniency programs can be effective in enhancing cartel detection and deterrence, but these effects are not straight-forward. It is even possible that there is an increase in the total number of cartels. Empirical evidence shows that the positive effect on cartel deterrence seems to dominate, but cannot provide definite evidence, as inference is derived only by detected cartels. This study uses a more direct measure of success, the intensity of competition at the industry level of OECD countries. An instrumental variable approach, reveals a positive effect on industries' competition intensity of leniency programs indicating effectiveness in cartel destabilization and effective deterrence.
Keywords: C23; K21; K42; L41; 330; Cartel; Antitrust; Leniency Program